Skin Diseases in Donkeys and Mules—An Update - Telma S. Lima; Raquel A. F. Silva; Raquel M. F. Pereira; Karoline L. Soares; Nayadjala T. A. Santos; Mônica S. Sousa; Fábio S. Mendonça; Ricardo B. Lucena (Animals, 2020)
The skin of donkeys and mules represents a promising source of income; however, cultural, productive, and infectious factors can directly interfere with the quality of the integumentary tissue and well-being of these species. The objective of this study is to present a literature review on equine dermatopathies. This literature review included scientific articles related to equine medicine and breeding according to pre-established search terms and expressions published in recently articles. The evaluation of the clinical and pathological behavior of dermatopathies implies the use of control strategies and the recognition of pathological patterns that may be particular to the species.